Regulatory focus predicts individual differences in pragmatic versus grammatical awareness and sensitivity - Zhang , Yiran; Papi, Mostafa (Studies in Second Language Learning and Teaching, 2024)
The present study employs regulatory focus theory (Higgins, 1997) to investigate the effects of L2 speakers’ chronic regulatory focus on their L2 pragmatic versus grammatical awareness. It involved the participation of 121 Chinese students, who are English language learners, at a university in the United States. Haws et al.’s (2010) questionnaire was used to examine the participants’ regulatory dispositions, and a judgment task was adapted from Bardovi-Harlig and Dörnyei (1998) to assess participants’ awareness of grammatical and pragmatic errors, as well as the severity of each type of error. Multiple regression results largely confirmed the predictions. Prevention regulatory focus, concerned with obligations, responsibilities, and negative outcomes, predicted L2 speakers’ recognition of grammatical errors and their severity. Conversely, promotion focus, which emphasizes growth, accomplishments, and positive outcomes, positively predicted L2 speakers’ perceptions of pragmatic error severity. These findings contribute to the understanding of how differences in chronic motivational orientations can lead to different L2 use patterns and characteristics.